PENGEMBANGAN VARIAN MOTIF BATIK GIRILAYU SEBAGAI DIVERSIFIKASI PRODUK FESYEN DAN HOME DÉCOR BAGI KELOMPOK BATIK GIRIARUM - SUHERLAN, YAYAN; Nurcahyanti, Desy; Bahari, Nooryan; Budi, Setyo; Amboro, Lulut; Wahyuingsih, Novita (Institut Seni Indonesia Surakarta, 2025)
Girilayu Batik as one of the leading creative industries in Karanganyar Regency has currently experienced quite rapid progress. Several studies and community service activities in an effort to increase product capacity and quality have been carried out, but along with the increasingly tight competition in the fashion market, product diversification is still needed to be adjusted to the functions and trends that are currently developing. The motifs and functions of batik products in Girilayu are considered to need development in order to reach the market from a different side. This community service activity is an effort to open up wider batik market opportunities. The purpose of this activity is so that creative batik industry players in the Giriarum Batik Group, Girilayu Village, are able to create batik motifs for fashion and home décor which are currently starting to be popular. The method used to achieve this goal is in the form of training and mentoring in exploring creative ideas and creating batik motifs that are in accordance with the tastes of potential consumers. Training and mentoring for batik product diversification which will be carried out supported by the technical skills already possessed by batik craftsmen in the Giriarum Batik Group will be able to create products that are in demand by consumers. Fashion products other than clothes and fabrics as well as home décor products will differentiate batik competitors, so that market opportunities are wide open.